2021
DOI: 10.3389/fpsyg.2021.743997
|View full text |Cite
|
Sign up to set email alerts
|

How to Improve Entrepreneurship Education in “Double High-Level Plan” Higher Vocational Colleges in China

Abstract: Entrepreneurship education complements vocational education in helping students develop their career prospects. This empirical study comprehensively analyzed sample data of 13,885 students from 40 “Double High-level Plan” higher vocational colleges in China using robust standard error regression analysis and other methods. The results showed that Entrepreneurship Practice (EP), Entrepreneurship Curriculum (EC), and Integration of Entrepreneurship Education and Professional Education (IEEPE) have a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…As future entrepreneurial practitioners, students must be adaptive to digital developments. This needs to be aligned with educators who have digital skills (Huang et al, 2021;Nurjamiah et al, 2020;Stadler & Smith, 2017). The passion for competition can influence students to always create innovations (Gazzola et al, 2020;Mielniczuk & Laguna, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As future entrepreneurial practitioners, students must be adaptive to digital developments. This needs to be aligned with educators who have digital skills (Huang et al, 2021;Nurjamiah et al, 2020;Stadler & Smith, 2017). The passion for competition can influence students to always create innovations (Gazzola et al, 2020;Mielniczuk & Laguna, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, vocational education students are excluded by high levels of industrial skill qualifications and low employment absorption (Arquisola & Muanar, 2019;Soputan, 2017). As a result, sustainable digital technology is urging entrepreneurship to contribute to reshaping the economic system (Brydges & Hracs, 2019;Huang et al, 2021). Facts in previous studies reveal that there is still a low desire of vocational education students to become entrepreneurs (Arquisola & Muanar, 2019;Kuat, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…"Double qualified" teachers refer to teachers with both professional knowledge and technical skills. In 2006, the Ministry of Education issued several opinions on improving the teaching quality of Higher Vocational Education in an all-round way, which proposed to gradually establish a "double qualified" teacher qualification certification system, and study and formulate the employment standards and access system for teachers in higher vocational colleges, marking that the construction of "double qualified" teachers has evolved into an important policy content (Huang et al, 2021).…”
Section: Promoting the Quality Of Talent Training By Optimizing The T...mentioning
confidence: 99%
“…(ii) Improve the teacher introduction evaluation mechanism and rights protection Teachers in vocational education undergraduate schools focus on the technical adaptability to industrial needs. They should fully control the "entry level", introduce a team of artisan teachers with rich practical work experience, form an accommodation mode of "double qualified" teachers coming from the enterprise and feeding the enterprise, and establish a cooperation and co construction mechanism between vocational education undergraduate teachers and enterprises (Huang et al, 2021). The school should give full play to the radiation and demonstration role of model teachers.…”
Section: (I)mentioning
confidence: 99%
“…Empirical research showed that different dimensions of entrepreneurial self-efficacy played a partial mediated and fully mediated role between the independent personality and entrepreneurial intention of migrant workers ( Chen et al, 1998 ; Wilson et al, 2007 ; Kasouf et al, 2015 ; Tantawy et al, 2021 ). However, most studies on entrepreneurial self-efficacy have focused on college students and corporate entrepreneurship ( Huang et al, 2021 ; Liu and Yu, 2021 ; Zelin et al, 2021 ), and, however, few scholars have studied farmers’ entrepreneurship in the context of rural revitalization in China. The article constructs a mechanistic model of farmers’ entrepreneurial behavior from the perspectives of entrepreneurial attitude and entrepreneurial environment, and uses a structural equation modeling approach to test it empirically in order to provide empirical support for the complex mechanisms among entrepreneurial attitude, entrepreneurial environment, entrepreneurial self-efficacy, and farmers’ entrepreneurial behavior.…”
Section: Introductionmentioning
confidence: 99%